The Need For Antistigma Services And Quality Of Life Of Schizophrenia At The Care For Soul Health City In Semarang City, Indonesia - Sri Endang Windiarti; Agus Soewandono; Zahroh Shaluhiyah; Annastasia Ediati (Publikasi Indonesia, 2022)
The Semarang City Government's efforts for the mental health village program have not been programmed intensively. The purpose of this study was to explore an urban care model for mental health in an effort to reduce stigma and improve the quality of life of people living with HIV. This research is a qualitative research with an exploratory descriptive approach. Data collection includes in-depth interviews with program stakeholders and direct observations of the program, as well as qualitative feedback from program participants. Based on the results of research using content analysis. The stages are: the text in the transcript, doing the unit of meaning, coding, categories so that the theme is obtained. Ethics clearance was obtained from the Faculty of Public Health, Diponegoro University, number: 579/EA/KEPK-FKM/2 Seven in-depth interviews were conducted representing different mental health programs. The service model in mental health care villages that is expected by the community is a form of intervention that aims to reduce stigma and improve the quality of life of Schizophrenia and prevent recurrence.